Mucoadhesive polysaccharides modulate sodium retention, release and taste perception. (1st February 2018) - Cook, Sarah L.; Woods, Samuel; Methven, Lisa; Parker, Jane K.; Khutoryanskiy, Vitaliy V.
Highlights: A potential role for mucoadhesive polysaccharides in food products is investigated. Mucoadhesion of a well-known food grade polysaccharide was established. Sensory tests show the mucoadhesive reduces saltiness in solution. Despite this reduction in perceived saltiness, the mucoadhesive retains more sodium ions for longer. Abstract: The mucoadhesion between polymeric substances and mucosal membranes, widely exploited in the pharmaceutics industry to prolong drug residence, has been investigated as a means of retaining taste or aroma molecules in the oral cavity. This study shows that the mucoadhesive properties of carboxymethyl cellulose, a commonly used polysaccharide in the food and pharmaceutics industry, can modify retention, release and perception of sodium over time. A three-part study was designed coupling in vitro retention using ex vivo porcine tongue, sensory perception with a trained panel and in vivo retention of sodium ions in human volunteers. The findings suggest that although salt perception is stunted in samples containing a random coil, ionic, mucoadhesive thickener, the retention of sodium ions in the mouth is prolonged due to the mucoadhesive nature of the polysaccharide. Not only has this study-investigated mucoadhesion of liquid formulations in the oral cavity but it is also the first to link the mucoadhesive nature of a commonly used polysaccharide to the organoleptic properties of a food.